Troubled roads: application of surface geophysics to highway failures of the sedimentary terrain (Iruekpen-Ifon road) of Edo State, Nigeria (2016)
As part of effort to examine the factors responsible for highway failure in the sedimentary terrain, geophysical survey involving Very Low Frequency Electromagnetic (VLF-EM), Schlumberger Vertical Electrical Sounding (VES), and dipole-dipole electrical resistivity techniques were carried out along Iruekpen-Ifon highway. This was aimed at using surface geophysics to characterize and identify the factors responsible the for road failures along Iruekpen-Ifon highway. ABEM WADI instrument was used to obtain electromagnetic-Very Low Frequency (VLF) field data, while ABEM resistivity meter was used to obtain electrical resistivity field data. The VLF-EM data were interpreted using the VLF Graphic software, VELFAN 1.0 double plot of filtered real and filtered imaginary against distance. The VES data obtained were interpreted using IP 2 Win software. Geoelectric parameters were used to generate the Dar Zarrouk second order parameters. 2-D inversion modeling of the dipole-dipole data was carried out using ZONDRES window software. VLF-EM result suggested varying degree of conductivity in the area and the wide spread of clay/metallic ore and water in the study area. Results show that the topsoil generally varies in composition from clay to clayey and laterite with resistivity values varying from 89 to 400 Ωm and thickness between 0.2 and 4.0 m. The fractured layers composed of clay and compacted clayey sand which represents the recent alluvial deposits with resistivity values of 2 to 89 Ωm and the thickness between 1.5 and 11 m. The fresh water zone is characterized by low resistivity ranging from 0.5 to 23 Ωm, which is diagnostic of saline water saturated with clay formation, fresh water ingression, and marls. The values of co-efficient of anisotropy () range from 1.03 to 2.19. The relatively higher values of λ (1.30 to 2.19) suggest that the subsurface rocks in these areas are likely to be more intensely fractured and more permeable. The saline water saturated with clay formation, fresh water ingression, fracture and marls clearly limit the lithological contacts and enhance high swelling potential which might be responsible for the road pavement failures in the studied area